Catalyzing Transcriptomics Research in Cardiovascular Disease: The CardioRNA COST Action CA17129 - Gomes, Clarissa Pedrosa da C; Ágg, Bence; Andova, Andrejaana; Arslan, Serdal; Baker, Andrew; Barteková, Monika; Beis, Dimitris; Betsou, Fay; Wettinger, Stephanie Bezzina; Bugarski, Branko; Condorelli, Gianluigi; Silva, Gustavo José Justo da; et al. (Non-coding RNA, 2019)
Cardiovascular disease (CVD) remains the leading cause of death worldwide and, despite continuous advances, better diagnostic and prognostic tools, as well as therapy, are needed. The human transcriptome, which is the set of all RNA produced in a cell, is much more complex than previously thought and the lack of dialogue between researchers and industrials and consensus on guidelines to generate data make it harder to compare and reproduce results. This European Cooperation in Science and Technology (COST) Action aims to accelerate the understanding of transcriptomics in CVD and further the translation of experimental data into usable applications to improve personalized medicine in this field by creating an interdisciplinary network. It aims to provide opportunities for collaboration between stakeholders from complementary backgrounds, allowing the functions of different RNAs and their interactions to be more rapidly deciphered in the cardiovascular context for translation into the clinic, thus fostering personalized medicine and meeting a current public health challenge. Thus, this Action will advance studies on cardiovascular transcriptomics, generate innovative projects, and consolidate the leadership of European research groups in the field.COST (European Cooperation in Science and Technology) is a funding organization for research and innovation networks (www.cost.eu).
Keywords: translational research; best practices and guidelines; personalized medicine; transcriptomics; cardiovascular disease